Voriconazole-Resistant Penicillium oxalicum: An Emerging Pathogen in Immunocompromised Hosts. (16th August 2014) - Chowdhary, Anuradha; Kathuria, Shallu; Agarwal, Kshitij; Sachdeva, Neelam; Singh, Pradeep K.; Jain, Sandeep; Meis, Jacques F.
Abstract: Penicillium species are rarely reported agents of infections in immunocompromised patients. We report 3 cases of invasive mycosis caused by voriconazole-resistant Penicillium oxalicum in patients with acute myeloid leukemia, diabetes mellitus, and chronic obstructive pulmonary disease, while on voriconazole therapy. Penicillium oxalicum has not been previously recognized as a cause of invasive mycoses.